2021
DOI: 10.1080/21670811.2021.1977668
|View full text |Cite
|
Sign up to set email alerts
|

Is Social Media Killing Local News? An Examination of Engagement and Ownership Patterns in U.S. Community News on Facebook

Abstract: This article focuses on two forces linked to declines in coverage of genuinely local civic affairs: (a) the impact of increasing corporate consolidation in ownership among news providers, and (b) the degree to which the economic incentives and logics of digital platforms may also drive editorial decision-making at news organizations away from coverage of local news. Using a unique dataset of 2.4 million Facebook posts published by local news organizations in three U.S. states between 2018 and 2019, we find evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 53 publications
1
19
0
2
Order By: Relevance
“…This result may potentially allude to the influence of ownership on the quality of local news content on social media. A recent study (Toff & Mathews, 2021) showed that while ownership mattered in the relationship between a local news channel's social media content and the level of audience engagement received, it was the frequency of posting local content that was an important predictor of audience engagement on Facebook. In our sample, ABC15 had the greatest number of CIN posts while NTV, the Sinclair-owned channel in our sample had the least number of CIN posts.…”
Section: Discussionmentioning
confidence: 99%
“…This result may potentially allude to the influence of ownership on the quality of local news content on social media. A recent study (Toff & Mathews, 2021) showed that while ownership mattered in the relationship between a local news channel's social media content and the level of audience engagement received, it was the frequency of posting local content that was an important predictor of audience engagement on Facebook. In our sample, ABC15 had the greatest number of CIN posts while NTV, the Sinclair-owned channel in our sample had the least number of CIN posts.…”
Section: Discussionmentioning
confidence: 99%
“…This is important as it measures whether the interest of the local media in coronavirus news changed as the pandemic evolved. Second, (RQ2) we analyzed the evolution of the public participation, given by the proportion of Facebook interactions that were associated to COVID-19 related news ( García-Perdomo et al, 2018 ; Toff and Mathews, 2021 ; Weber et al, 2019 ). This is relevant as it can shed light on whether the audience interest in COVID-19 progressed throughout the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…We frame our analysis in the context of local journalism as it plays a critical role in keeping the public properly informed. Local news organizations are currently under immense financial pressure ( Jenkins and Nielsen, 2020 ; Olsen et al, 2020 ) and if they are to survive, then they need to understand the dynamics of local news consumption, evaluation, and dissemination in social media ( Almgren, 2017 ; Toff and Mathews, 2021 ; Olsen, 2021 ; Thorson et al, 2020 ). A cataclysmic crisis like the COVID-19 presents a cogent opportunity for doing so.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations